Prevalence of herpes -, measles morbillivirus-, parvovirus B19 - and rubella viruses immunoglobulin G among women with chronic hepatitis B of reproductive age in Denmark: A cross-sectional study. (December 2020) - Bergløv, Anne; Hallager, Sofie; Panum, Inge; Weis, Nina
Highlights: IgG against vertically transmitted viruses generally high among women with chronic hepatitis B. Seroprevalence differed among women with respect to region of origin. Generally small differences in seroprevalence compared to background population. Women with chronic hepatitis B can follow general antenatal care in Denmark. Abstract: Objectives: The aim of this study was to investigate whether the seroprevalence of IgG antibodies against seven viruses (cytomegalovirus, herpes simplex virus 1&2, measles morbillivirus, parvovirus B19, rubella, and varicella-zoster virus), which can potentially compromise maternal and fetal wellbeing, differs based on country of origin among women with chronic hepatitis B (CHB). Method: This study was a single-center, hospital-based cross-sectional study. The study included women with CHB 15–45 years of age, included in the Danish Database for Hepatitis B and C. Seroprevalence estimates were calculated with a 95% confidence interval and were compared between age groups, regions of origin, and to the general population. Results: 177 women were included in the study. Overall, the seroprevalences of antibodies were similar among women with CHB with origin outside Denmark and compared to the general population in Denmark, but there was a notable difference in the seroprevalence of antibodies against herpes simplex 2 between women from Africa (37.1% CI 95% 22.0;55.1) and women from the Middle East (2.5% CI 95% 0.1;14.7). Conclusion: Women with CHB whose origin is outside Denmark do not appear to differ, based on origin, or be at greater risk of acquiring these viruses during pregnancy than their Danish counterparts.